Analisis Peran Relawan Pajak Dalam Meningkatkan Kepatuhan Pelaporan Wajib Pajak Orang Pribadi - Ava Indriani; Utaminingtyas, Tri Hesti; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This research aims to analyze the role of tax volunteers in 2023 in increasing individual taxpayer reporting compliance at KPP Pratama Pasar Rebo. The research method used in this research is qualitative descriptive analysis. The choice of qualitative research design in this study was to reveal events and facts that are relevant to the research title, so that the author can represent the data that has been collected regarding the role of tax volunteers in increasing wpop reporting compliance at KPP Pratama Pasar Rebo. The analysis technique used in this research is a qualitative analysis technique. Data collection techniques were carried out using observation, interview and documentation techniques. The research results show that the involvement of tax volunteers in reporting the Annual SPT at KPP Pratama Pasar Rebo has a very important role. The involvement of tax volunteers is considered very helpful and has a positive impact on taxpayers' understanding, shortens queuing time, and increases reporting efficiency. Similarly, based on documentation and interviews conducted by researchers with Tax Extension Staff, Tax Volunteers from Uhamka and Tax Volunteer Advisors, it shows that the services provided by tax volunteers can realize wpop compliance in reporting Annual Tax Returns. However, the increase in individual taxpayers with the involvement of tax volunteers in reporting Annual Tax Returns at KPP Pratama Pasar Rebo still requires improvement. This shows that there are still obstacles and needs for improvement in increasing the effectiveness of tax volunteer involvement, socialization is not yet optimal, tax volunteer skills development is low, and aspects of service quality still need to be improved.